Analysis of The Critical Thinking Style of Prospective Biology Teachers Students - Jayanti Syahfitri (Postgraduate, University of Mataram, 2023)
A person's critical thinking style will determine the extent of critical thinking skills. This study examines differences in the critical thinking styles of biology teacher candidates based on academic level. The method applied in this study is non-experimental with a comparative design. The instrument used was the Yanpiaw Creative-Critical Style Test, which was given to several prospective biology teacher students from semester 2, semester 4, semester 6, and semester 8 as respondents. The results showed that there was a significant difference between the average critical thinking style between students in semester 2 and semester 6 (sig. 0.011 < 0.05) and between semester 2 and semester 8 (sig. 0.029 < 0.05). Based on the findings, it can be concluded that academic level or level does not always affect a person's critical thinking style. However, it is also possible due to academic majors, behavior style, and ethnicity (culture). Therefore, an educator needs to provide learning methods and media that can support the development of students' critical thinking styles.